No evidence for a direct effect of von Willebrand factor's ABH blood group antigens on von Willebrand factor clearance - Groeneveld, D. J.; Bekkum, T.; Cheung, K. L.; Dirven, R. J.; Castaman, G.; Reitsma, P. H.; Vlijmen, B.; Eikenboom, J. (Journal of thrombosis and haemostasis, 2015)
Summary Background One of the major determinants of von Willebrand factor (VWF) plasma levels is ABO blood group status, and individuals with blood group O have ~ 25% lower plasma levels. The exact mechanism behind this relationship remains unknown, although effects on clearance have been postulated. Objectives To determine whether clearance of VWF is directly dependent on the presence of ABH antigens on VWF. Methods Three type 3 von Willebrand disease (VWD) patients were infused with Haemate‐P, and the relative loading of VWF with ABH antigens at different time points was measured. VWF‐deficient mice were injected with purified plasma‐derived human VWF obtained from donors with either blood group A, blood group B, or blood group O. Results In mice, we found no difference in clearance rate between plasma‐derived blood group A, blood group B and blood group O VWF. Faster clearance of the blood group O VWF present in Haemate‐P infused in type 3 VWD patients would have resulted in a relative increase in the loading of VWF with A and B antigens over time. However, we observed a two‐fold decrease in the loading with A and B antigens in two out of three patients, and stable loading in the third patient. Conclusion There is no direct effect of ABH antigens on VWF in VWF clearance. We demonstrate that, in a direct comparison within one individual, blood group O VWF is not cleared faster than blood group A or blood group B VWF. Clearance differences between blood group O and non‐blood group O individuals may therefore be related to the blood group status of the individual rather than the ABH antigen loading on VWF itself.